Pengelolaan Operasional Water Treatment Sebagai Upaya Peningkatan Proses Pengolahan Air Sungai - Puja Widikda, Aris; Mujayyin, Farid (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
Water sources such as rivers, lakes, and reservoirs often have quality issues, making them unsuitable for daily human use. Despite ongoing government and societal efforts to control waste and reduce pollution, water treatment remains critical to ensure its suitability for consumption. Effective water resource management requires specialized skills, including design, technical implementation, operational capabilities, and maintenance. Post-construction, water treatment projects frequently face issues such as substandard operations and inadequate maintenance. This study explores methods to enhance river water quality through improved operational management and maintenance. Key improvements involve regular equipment inspections, planned operations, and diligent maintenance control. Findings indicate that equipment performance is within acceptable ranges, with average motor vibration at 0.25, engine temperature at 49.3°C, and engine speed at 1230 rpm. Water quality after treatment shows a pH of 7.71 NTU, demonstrating that operational and maintenance standards are being met effectively.